Patients with unexplained mismatch repair deficiency are interested in updated genetic testing - Jessica Omark; Eduardo Vilar; Y Nancy You; Leslie Dunnington; Sarah Noblin; Blair Stevens; Maureen Mork (Hereditary Cancer in Clinical Practice, 2020)
Abstract Background Individuals who have colorectal or endometrial cancers displaying loss of immunohistochemical staining of one or more mismatch repair proteins without an identifiable causative germline pathogenic variant have unexplained mismatch repair deficiency (UMMRD). Comprehensive germline genetic testing for Lynch syndrome (LS) includes sequencing and deletion/duplication analysis of MLH1, MSH2, MSH6, and PMS2, deletion analysis of EPCAM, and MSH2 inversion analysis. Updated genetic testing to include elements of comprehensive LS testing not previously completed could further clarify LS status in individuals with UMMRD, allowing for tailored screening guidelines for affected individuals and their family members. However, patient understanding of the potential impact of updated genetic testing for LS is unclear. This study aimed to evaluate the interest in and perceived impact of updated genetic testing among individuals with UMMRD at a tertiary academic center. Methods A survey evaluating interest in and perceived impact of updated genetic testing was mailed to 98 potential participants. Electronic health record review was completed for all individuals meeting eligibility criteria. Thirty-one individuals responded to the survey. Results Results indicate this population is highly interested in updated genetic testing with the perceived impact being primarily for family members to have appropriate genetic testing and screening. Electronic health record review indicates that clinicians have an evolving understanding of causes of UMMRD, representing a potential change in assessment of cancer risk. Conclusions Updated risk assessment and genetic counseling with a discussion of the benefits and limitations of germline and somatic genetic testing, is essential as the understanding of UMMRD and genetic testing recommendations for this population evolve.